ANALISIS KEMAMPUAN MANAGERIAL DAN PENDAPATAN UMKM BERBASIS WISATA KULINER DI KABUPATEN BONE BOLANGO - Mohamad Andre Hulukati; Supriyo Imran; Mohammad Zubair Hippy (PT. Hasba Edukasi Mandiri, 2025)
Micro, Small and Medium Enterprises (MSMEs) Culinary tourism is one of the economic bases of the Bone Bolango Regency community which is starting to become the foundation for economic improvement, so that it can compete with other regions in Gorontalo Province. The purpose of this research is to find out 1) How is the managerial ability of culinary tourism-based MSME players in Bonelango Regency, 2) How is the income of culinary tourism-based MSME players in Bone Bolango Regency, 3) How does managerial ability affect the income of MSME players. The research method used is descriptive quantitative with simple linear regression analysis which is used to see if there is a relationship between the managerial skills of culinary tourism MSME players and income. The results showed that there is a positive relationship between the managerial skills of culinary tourism MSME players in Bone Bolango Regency and income. This means that culinary tourism MSMEs in Bone Bolango Regency are classified as good and have a positive effect on income. The better the managerial skills of business actors, the more stable and increased income is obtained.